Pengaruh Inovasi Produk dan Labelisasi Halal Terhadap Loyalitas Pelanggan pada Japanese Pancake di Kota Pontianak - Intan, Intan; Yulia, Yulia; Saragih, Eka Junila (Jurnal Keuangan dan Perbankan Syariah, 2023)
The aims of this study were (1) to analyze the effect of productinnovation on customer loyalty at Japanese Pancakes in Pontianak City. (2) To analyze the effect of halal labeling oncustomer loyalty to Japanese Pancakes in Pontianak City. (3) To analyze the effect of product innovation and halal labelingon customer loyalty to Japanese Pancakes in Pontianak City. This research approach is a quantitative research and the typeof research is an associative type with a sample of 100 respondents or customers in Japanese Pancake Pontianak City. The results of this study note that product innovation has a positive and significant effect on customer loyalty, halal labeling has a positive and significant effect on customerloyalty, then product innovation and halal labelingsimultaneously or simultaneously have an effect on customerloyalty.